Potensi Lendir Ikan Lele (Clarias gariepinus) Dan Kolagen Sisik Ikan Bandeng (Chanos Chanos) Sebagai Serum Anti Jerawat - Wahyuni, Yuyun Sri; Thahir, Zakiah (Media Farmasi XXX, 2023)
Potential Mucus Catfishes (Clarias gariepinus) and Collagen Scales Milkfish (Chanos chanos) asSerumAntiAcneAlong with the times, acne which was once considered a normal condition has now been classified as a chronic disease that psychologically affects the quality of life. The serum is a preparation with concentrated active ingredients and a small amount of solvent content. With its low viscosity, it delivers active substances through the skin's surface by forming a thin film so that the effect is absorbed more quickly by the skin, providing a more comfortable effect, and spreading more easily on the skin's surface. The purpose of this study was to make an anti-acne serum from catfish mucus (Clarias gariepinus) and milkfish scale collagen (Chanos chanos) and to test the physical quality of serum preparations, including organoleptic, homogeneity, pH, viscosity, spreadability and adhesion. In this study, 4 formulas were made, namely, formula 1 consisting of a base, formula 2 containing the active substance of catfish slime, formula 3 containing the active substance of milkfish scale collagen, and formula 4 consisting of a combination of the active substance of catfish slime and milkfish scale collagen. The results showed that anti-acne serum from catfish mucus (Clarias gariepinus) and milkfish scale collagen (Chanos chanos) had met the physical quality requirements of serum preparations and could inhibit the growth of Staphylococcus aureus bacteria with an inhibitory zone of 28.33 mm and the preparation did not cause irritation to the skin.Keywords: Antiacne, Clarias gariepinus, Chanos, SerumSeiring berkembangnya zaman, jerawat yang dulunya dianggap sebagai kondisi normal kini telah tergolong ke dalam penyakit yang kronik yang berpengaruh secara psikologis terhadap kualitas hidup. Serum merupakan sediaan dengan konsentrasi bahan aktif konsentrat dan sedikit kandungan pelarut. Dengan viskositasnya yang rendah menghantarkan zat aktif melalui permukaan kulit dengan membentuk lapisan film tipis sehingga efeknya lebih cepat diserap kulit, memberikan efek yang lebih nyaman dan lebih mudah menyebar di permukaan kulit. Tujuan dari penelitian ini adalah untuk membuat serum anti jerawat dari lendir ikan lele (Clarias gariepinus) dan kolagen sisik ikan bandeng (Chanos chanos) dan untuk menguji mutu fisik sediaan serum, meliputi organoleptik, homogenitas, pH, viskositas, daya sebar dan daya lekat. Pada penelitian ini dibuat 4 formula yaitu formula 1 hanya terdiri dari basis, formula 2 mengandung zat aktif lendir lele, formula 3 mengandung zat aktif kolagen sisik ikan bandeng, dan formula 4 terdiri dari kombinasi zat aktif lendir lele dan kolagen sisik ikan bandeng. Dari hasil penelitian diperoleh bahwa serum anti jerawat dari lendir ikan lele (Clarias gariepinus) dan kolagen sisik ikan bandeng (Chanos chanos) telah memenuhi persyaratan mutu fisik sediaan serum, dapat menghambat pertumbuhan bakteri Staphylococcus aureus dengan zona hambat sebesar 28,33 mm serta sediaan tidak menyebabkan iritasi pada kulit.Kata kunci : Anti jerawat, Clarias gariepinus, Chanos chanos, Serum.